Sustained Release Bioadhesive Suppository Formulation for Systemic Delivery of Ornidazole: In-silico Docking Study - Dash, Rasmita; Sahoo, Rudra Narayan; Nandi, Souvik; Swain, Rakesh; Mallick, Subrata (Indian Journal of Pharmaceutical Education and Research, 2019)
Background and Objectives: Ornidazole is widely used as an antiprotozoal and antiamoebic drug and its onset of action is within 2 h. The major extent of the drug is metabolized in the liver and excreted in the urine and faeces. Hence, the present study of suppository formulation for sustained systemic delivery of ornidazole is significant which could minimize abdominal disturbances and nausea and delayed onset of action particularly after oral administration. Methods: Bioadhesive suppository formulations were prepared for systemic delivery of ornidazole via rectal and vaginal route. Results: The physical drug-excipient-interaction was confirmed by in-silico docking study. The affinity between drug-HPMC and drug-PEG was found to be -2 and -0.9 k cal/mol respectively. In vitro drug release of the suppositories varied depending on the viscosity grade of HPMC used and all have followed mostly diffusion controlled mechanism. The formulation containing HPMC K100 showed the most sustained release of ornidazole in both the dissolution fluid of pH 7.4 and 4.5 (54.53 and 41.89 % respectively after 360 min). Conclusion: In conclusion, present bio adhesive suppositories could be utilized for sustained systemic delivery of ornidazole via rectal and vaginal route. The findings of this work will contribute to the current knowledge and encourage future pre-clinical research.
Keywords: Ornidazole; Sustained release suppository; In-silico docking; Bioadhesive; formulation; in-vitro dissolution